The efficacy and safety of irreversible electroporation for the ablation of renal masses: a prospective, human, in-vivo study protocol - Wagstaff, Peter GK (BMC Cancer, 2015)
BACKGROUND: Electroporation is a novel treatment technique utilizing electric pulses, traveling between two or more electrodes, to ablate targeted tissue. The first in human studies have proven the safety of IRE for the ablation of renal masses. However the efficacy of IRE through histopathological examination of an ablated renal tumour has not yet been studied. Before progressing to a long-term IRE follow-up study it is vital to have pathological confirmation of the efficacy of the technique. Furthermore, follow-up after IRE ablation requires a validated imaging modality. The primary objectives of this study are the safety and the efficacy of IRE ablation of renal masses. The secondary objectives are the efficacy of MRI and CEUS in the imaging of ablation result. METHODS/DESIGN: 10 patients, age ≥ 18 years, presenting with a solid enhancing mass, who are candidates for radical nephrectomy will undergo IRE ablation 4 weeks prior to radical nephrectomy. MRI and CEUS imaging will be performed at baseline, one week and four weeks post IRE. After radical nephrectomy, pathological examination will be performed to evaluate IRE ablation success. DISCUSSION: The only way to truly assess short-term (4 weeks) ablation success is by histopathology of a resection specimen. In our opinion this trial will provide essential knowledge on the safety and efficacy of IRE of renal masses, guiding future research of this promising ablative technique. TRIAL REGISTRATION: Clinicaltrials.gov registration number NCT02298608. Dutch Central Committee on Research Involving Human Subjects registration number NL44785.018.13